Method for producing non-aqueous secondary battery electrode slurry and method for producing non-aqueous secondary battery electrode
The use of a water-soluble electrode binder with tailored surface free energy components addresses binding issues in non-aqueous secondary batteries, resulting in electrodes with reduced cracks, improved peel strength, and lower internal resistance for enhanced battery performance.
Patent Information
- Application Number
- JP2021115745
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-24
- Filing Date
- 2021-07-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-10-22
AI Technical Summary
Existing non-aqueous secondary battery electrodes face issues with insufficient binding properties between active materials and current collectors, leading to peeling and cracks, which reduce capacity and increase internal resistance, while current binders like PVDF and sodium acrylate-N-vinylacetamide copolymers have limitations in film thickness and manufacturing costs.
A non-aqueous secondary battery electrode slurry manufacturing method using a water-soluble electrode binder with specific surface free energy components, including a resin component with ethylenically unsaturated bonds, to enhance binding properties and reduce cracks, ensuring high peel strength and low internal resistance.
The method results in electrodes with fewer cracks, higher peel strength, lower internal resistance, and improved cycle characteristics, enhancing the performance and efficiency of non-aqueous secondary batteries.
Smart Images

Figure 0007608991000009 
Figure 0007608991000010 
Figure 0007608991000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous secondary battery electrode. Method for producing slurry and non-aqueous secondary battery electrodes Manufacturing method Regarding. [Background technology]
[0002] Secondary batteries using non-aqueous electrolytes (non-aqueous secondary batteries) are superior to secondary batteries using aqueous electrolytes in terms of high voltage, small size, and weight reduction. Therefore, non-aqueous secondary batteries are widely used as power sources for notebook computers, mobile phones, power tools, and electronic and communication devices. Recently, non-aqueous secondary batteries have also been used for electric vehicles and hybrid vehicles from the perspective of environmentally friendly vehicle applications, but there is a strong demand for higher output, higher capacity, and longer life. A representative example of a non-aqueous secondary battery is the lithium-ion secondary battery.
[0003] The non-aqueous secondary battery includes a positive electrode having an active material such as a metal oxide, a negative electrode having an active material such as a carbon material such as graphite, and a non-aqueous electrolyte solvent mainly composed of carbonates or a flame-retardant ionic liquid. The non-aqueous secondary battery is a secondary battery in which ions move between the positive electrode and the negative electrode to charge and discharge the battery. In detail, the positive electrode is obtained by applying a slurry made of a metal oxide and a binder to the surface of a positive electrode current collector such as an aluminum foil, drying the slurry, and then cutting the slurry to an appropriate size. The negative electrode is obtained by applying a slurry made of a carbon material and a binder to the surface of a negative electrode current collector such as a copper foil, drying the slurry, and then cutting the slurry to an appropriate size. The binder serves to bind the active materials to each other and to the current collector in the positive electrode and the negative electrode, and to prevent the active material from peeling off from the current collector.
[0004] A well-known binder is a polyvinylidene fluoride (PVDF)-based binder that uses an organic solvent, N-methyl-2-pyrrolidone (NMP), as the solvent. However, this binder has low binding properties between active materials and between active materials and current collectors, and requires a large amount of binder for practical use. This has the drawback of reducing the capacity of non-aqueous secondary batteries. In addition, since the binder uses NMP, an expensive organic solvent, it has been difficult to reduce manufacturing costs.
[0005] Patent Document 1 discloses an ink mixture for forming a secondary battery electrode, which contains carboxymethyl cellulose, a water-dispersible binder, and water. Patent Document 2 discloses a non-aqueous battery electrode binder containing a sodium acrylate-N-vinylacetamide copolymer (copolymerization ratio: sodium acrylate / N-vinylacetamide=10 / 90 mass ratio). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-023015 A [Patent Document 2] International Publication No. 2017 / 150200 [Non-patent literature]
[0007] [Non-Patent Document 1] Yasuaki Kitazaki, Toshio Hata, Journal of the Japan Adhesion Association, vol.8, 131-141 (1972) Summary of the Invention [Problem to be solved by the invention]
[0008] The water-dispersible binder disclosed in Patent Document 1 requires the use of carboxymethyl cellulose as a thickener, and the slurry preparation process is complicated. Furthermore, even this binder does not provide sufficient binding between active materials and between the active material and the current collector, and when an electrode is produced using a small amount of binder, there is a problem that part of the active material peels off during the process of cutting the current collector.
[0009] The sodium acrylate-N-vinylacetamide copolymer disclosed in Patent Document 2 has a problem in that many cracks occur in electrodes with large film thickness, that is, electrodes with large basis weight.
[0010] Therefore, the present invention provides a non-aqueous secondary battery electrode that has an electrode active material layer with few cracks and high peel strength against a current collector, and can provide a secondary battery with low internal resistance and good cycle characteristics. Method for producing slurry and non-aqueous secondary battery electrodes Manufacturing method The purpose is to provide. [Means for solving the problem]
[0011] In order to solve the above problems, the present invention provides the following [1] to [ 13 ] is as follows. [1] A method for producing a non-aqueous secondary battery electrode slurry, comprising a step of mixing an electrode active material (A), an electrode binder (B), and an aqueous medium, The electrode binder (B) is composed of a water-soluble component containing a resin component, The surface free energy γ of the electrode binder (B) at 23° C. B is 70mJ / m 2 is as follows: The dipole component of the surface free energy γ p B is 26 mJ / m 2 A method for producing a non-aqueous secondary battery electrode slurry, comprising: [2] The surface free energy γ B is 66mJ / m 2 The non-aqueous secondary battery electrode according to [1] below: Method for producing slurry . [3] The dipole component γ of the surface free energy p B is 22 mJ / m 2The non-aqueous secondary battery electrode according to [1] or [2], Method for producing slurry . [4] The hydrogen bond component of the surface free energy, γ h B is 24 mJ / m 2 A non-aqueous secondary battery electrode according to any one of [1] to [3] below: Method for producing slurry . [5] The nonaqueous secondary battery electrode according to any one of [1] to [4], wherein the resin component contains a polymer of a compound having an ethylenically unsaturated bond. Method for producing slurry . [6] A non-aqueous secondary battery electrode comprising a current collector and an electrode active material layer. Manufacturing method And, A step of mixing an electrode active material (A), an electrode binder (B), and an aqueous medium to obtain an electrode slurry; and applying the electrode slurry onto a current collector and drying the electrode slurry to obtain the electrode active material layer. The electrode binder (B) is composed of a water-soluble component containing a resin component, The surface free energy γ of the electrode binder (B) at 23° C. B is 70mJ / m 2 is as follows: The dipole component of the surface free energy γ p B is 26 mJ / m 2 A method for producing a non-aqueous secondary battery electrode, comprising: [7] The electrode active material layer is (A) The non-aqueous secondary battery electrode according to [6], which contains 85% by mass or more and 99% by mass or less of Manufacturing method . [8] The electrode active material (A) The non-aqueous secondary battery electrode according to [6] or [7], which comprises a material containing an Si element and a carbon material. Manufacturing method . [9] The nonaqueous secondary battery electrode according to any one of [6] to [8], wherein the electrode active material layer has a peel strength from the current collector of 30 mN / mm or more. Manufacturing method .
[10] The surface free energy γ B is 66mJ / m 2 Is less than or equal to [6] ~ [9] 13. A method for producing a non-aqueous secondary battery electrode according to claim 12.
[11] The dipole component γ of the surface free energy pB is 22 mJ / m 2 Is less than or equal to [6] ~
[10] The method for producing a non-aqueous secondary battery electrode according to any one of the preceding claims. .
[12] The hydrogen bond component γ of the surface free energy h B is 24 mJ / m 2 Is less than or equal to [6] ~
[11] 13. A method for producing a non-aqueous secondary battery electrode according to claim 12.
[13] The resin component contains a polymer of a compound having an ethylenically unsaturated bond. [6] ~
[12] 13. A method for producing a non-aqueous secondary battery electrode according to claim 12. Effect of the Invention
[0012] According to the present invention, a non-aqueous secondary battery electrode can be obtained which has an electrode active material layer with few cracks and high peel strength against a current collector, and which has low internal resistance and good cycle characteristics. Method for producing slurry and non-aqueous secondary battery electrodes Manufacturing method can be provided. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a diagram plotting the number of cracks in an electrode active material layer against the surface free energy γ B of an electrode binder (B) according to an example and a comparative example of the present invention. [Diagram 2] FIG. 1 is a diagram plotting the number of cracks in an electrode active material layer against the dipole component γp B of the surface free energy γ B of an electrode binder (B) according to an example and a comparative example of the present invention. [Diagram 3] FIG. 1 is a diagram plotting the number of cracks in an electrode active material layer against the dispersion force component γd B of the surface free energy γ B of an electrode binder (B) according to an example and a comparative example of the present invention. [Figure 4] FIG. 1 is a diagram plotting the number of cracks in an electrode active material layer against the hydrogen bond component γh B of the surface free energy γ B of an electrode binder (B) according to an example and a comparative example of the present invention. [Diagram 5]FIG. 1 is a diagram in which values of peel strength of an electrode active material layer are plotted against surface free energy γ B of an electrode binder (B) according to an example of the present invention and a comparative example. [Figure 6] FIG. 1 is a diagram in which values of peel strength of an electrode active material layer are plotted against the dipole component γpB of the surface free energy γB of an electrode binder (B) according to an example and a comparative example of the present invention. [Figure 7] FIG. 1 is a diagram in which values of peel strength of an electrode active material layer are plotted against the dispersion force component γd B of the surface free energy γ B of an electrode binder (B) according to an example of the present invention and a comparative example. [Figure 8] FIG. 1 is a diagram in which values of peel strength of an electrode active material layer are plotted against hydrogen bond component γh B of surface free energy γ B of an electrode binder (B) according to an example and a comparative example of the present invention. [Figure 9] FIG. 1 is a diagram in which the discharge capacity retention rate of a battery is plotted against the surface free energy γ B of the electrode binder (B) according to an example of the present invention and a comparative example. [Figure 10] FIG. 1 is a diagram in which the values of the discharge capacity retention rate of a battery are plotted against the dipole component γp B of the surface free energy γ B of the electrode binder (B) according to the examples and comparative examples of the present invention. [Figure 11] FIG. 1 is a diagram in which the values of the discharge capacity retention rate of a battery are plotted against the dispersion force component γd B of the surface free energy γ B of the electrode binder (B) according to the examples of the present invention and the comparative examples. [Figure 12] FIG. 1 is a diagram in which the values of the discharge capacity retention rate of a battery are plotted against the hydrogen bond component γh B of the surface free energy γ B of the electrode binder (B) according to the examples and comparative examples of the present invention. [Figure 13] FIG. 1 is a diagram plotting the DCR value of a battery against the surface free energy γ B of the electrode binder (B) according to an embodiment of the present invention and a comparative example. [Figure 14] FIG. 1 is a diagram plotting the DCR value of a battery against the dipole component γp B of the surface free energy γ B of an electrode binder (B) according to an example and a comparative example of the present invention. [Figure 15]FIG. 1 is a diagram plotting the DCR value of a battery against the dispersion force component γd B of the surface free energy γ B of the electrode binder (B) according to the examples and comparative examples of the present invention. [Figure 16] FIG. 1 is a diagram plotting the DCR value of a battery against the hydrogen bond component γh B of the surface free energy γ B of an electrode binder (B) according to an embodiment of the present invention and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described in detail. In this embodiment, the nonaqueous secondary battery is a secondary battery in which ions that become charge carriers move between the positive electrode and the negative electrode during charging and discharging. The positive electrode includes a positive electrode active material, and the negative electrode includes a negative electrode active material. These electrode active materials are materials that can intercalate and deintercalate ions. A preferred example of a secondary battery having such a configuration is a lithium ion secondary battery.
[0015] In the following description, unless otherwise specified, "surface" means "surface".
[0016] "(Meth)acrylic acid" refers to either or both of methacrylic acid and acrylic acid. "(Meth)acrylate" refers to either or both of methacrylate and acrylate. "(Meth)acrylonitrile" refers to either or both of methacrylonitrile and acrylonitrile.
[0017] The "non-volatile content" contained in a mixture (e.g., a slurry or a composition) refers to components with a boiling point of 130°C or less at 1 atmosphere (1013 hPa). The "non-volatile content concentration" of a mixture refers to the proportion (mass%) of components contained in the mixture that have a boiling point of 130°C or more at 1 atmosphere (1013 hPa).
[0018] In the present invention, the surface free energy, its dispersion force component, dipole component, and hydrogen bond component are values at 23° C. unless otherwise specified.
[0019] <1. Nonaqueous secondary battery electrode> The nonaqueous secondary battery electrode (hereinafter, sometimes referred to as "electrode") according to this embodiment includes a current collector and an electrode active material layer formed on the current collector. The shape of the electrode is, for example, a laminate or a wound body, but is not particularly limited.
[0020] [1-1. Current collector] The current collector is preferably a metal sheet having a thickness of 0.001 to 0.5 mm, and examples of the metal include iron, copper, aluminum, nickel, stainless steel, etc. When the nonaqueous secondary battery electrode is a negative electrode of a lithium ion secondary battery, the current collector is preferably a copper foil.
[0021] [1-2. Electrode active material layer] The electrode active material layer according to this embodiment includes an electrode active material (A) and an electrode binder (B). In addition to these components, the electrode active material layer may include a conductive assistant, etc. The peel strength of the electrode active material layer to the current collector is preferably 30 mN / mm or more, more preferably 40 mN / mm or more, and even more preferably 50 mN / mm or more. This is to prevent the electrode active material layer from peeling off from the current collector due to manufacturing processes such as the electrode processing process and the battery assembly process, and external forces applied to the battery, etc.
[0022] [1-2-1. Electrode active material (A)] The electrode active material (A) is a material capable of inserting and desorbing ions that serve as charge carriers. For example, when the charge carriers are lithium ions, the nonaqueous secondary battery is a lithium ion secondary battery. In the electrode active material layer, the content of the electrode active material (A) is preferably 85% by mass or more, more preferably 90% by mass or more, and even more preferably 92% by mass or more. This is to increase the insertion / desorption capacity of the charge carriers in the electrode and increase the charge / discharge capacity of the nonaqueous secondary battery.
[0023] In the electrode active material layer, the content of the electrode active material (A) is preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97% by mass or less, in order to contain the electrode binder (B) in the electrode active material layer (the effect of which will be described later).
[0024] "1-2-1-1. Negative electrode active material" When the non-aqueous secondary battery electrode is the negative electrode of a lithium ion secondary battery, examples of the negative electrode active material include carbon materials, lithium titanate, silicon, silicon compounds, etc. Examples of carbon materials include cokes such as petroleum coke, pitch coke, and coal coke; carbides of organic compounds; and graphites such as artificial graphite and natural graphite. Examples of silicon compounds include SiOx (0.1≦x≦2.0). Note that the negative electrode active material may be a composite of two or more of the materials listed here.
[0025] The negative electrode active material preferably contains a material containing Si element and a carbon material. This is because the charge / discharge capacity increases while maintaining good cycle characteristics of the non-aqueous secondary battery. It is more preferable to use a composite material of SiOx and a carbon material, or a composite material of silicon and a carbon material (Si / graphite) as the negative electrode active material. It is even more preferable that the carbon material contains graphite. This is because it is highly effective in improving the binding property of the negative electrode active material by the electrode binder (B). Here, the composite material may form covalent bonds, hydrogen bonds, etc. between two or more substances, but may not form these bonds. In addition, a specific example of artificial graphite is SCMG (registered trademark)-XRs (manufactured by Showa Denko K.K.).
[0026] "1-2-1-2. Cathode active material" When the non-aqueous secondary battery electrode is a positive electrode of a lithium ion secondary battery, examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium composite oxides containing nickel, spinel-type lithium manganese oxide (LiMn2O4), olivine-type lithium iron phosphate, and chalcogen compounds such as TiS2, MnO2, MoO3, and V2O5. The positive electrode active material may contain any of these compounds alone or may contain a plurality of types. Oxides of other alkali metals may also be used. Examples of lithium composite oxides containing nickel include Ni-Co-Mn-based lithium composite oxides, Ni-Mn-Al-based lithium composite oxides, and Ni-Co-Al-based lithium composite oxides. Specific examples of the positive electrode active material include LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 and LiNi 3 / 5 Mn 1 / 5 Co 1 / 5 Some examples include:
[0027] [1-2-2. Electrode binder (B)] The electrode binder (B) according to this embodiment is a water-soluble binder containing a resin component. The electrode binder (B) according to this embodiment is used to bind the electrode active materials (A) together and between the electrode active material (A) and a current collector. In the electrode active material layer, the content of the electrode binder (B) is preferably 1.0 mass% or more, more preferably 3.0 mass% or more. This is to suppress the electrode active material (A) from slipping off and improve the peel strength of the electrode active material layer. In the electrode active material layer, the content of the electrode binder (B) is preferably 12.0 mass% or less, more preferably 7.0 mass% or less. This is to increase the charge / discharge capacity of the battery by including more electrode active material (A) in the electrode active material layer.
[0028] "1-2-2-1. Surface free energy of electrode binder (B)" Surface free energy γ of electrode binder (B) at 23℃ B is 70mJ / m 2 Less than 66 mJ / m 2It is preferable that the concentration is less than 55 mJ / m 2 More preferably, it is 40 mJ / m or less. 2 It is more preferable that the content be equal to or less than 100%, since this makes it possible to reduce the DCR of the battery.
[0029] The surface free energy γ is the dispersion force component γ d , dipole component γ p , and the hydrogen bond component γ h That is, γ = γ d +γ p +γ h The surface free energy of the electrode binder (B) γ B Of these, the dipole component γ p B The value is 26 mJ / m 2 This is because the DCR of the battery can be reduced and the discharge capacity retention rate of the battery can be increased. p B The value is 22 mJ / m 2 Preferably, it is 19 mJ / m or less. 2 More preferably, it is 10 mJ / m or less. 2 It is more preferable that the DCR of the battery is equal to or less than 100 μm.
[0030] Surface free energy γ of electrode binder (B) B Among them, the hydrogen bond component γ h B The value is 24 mJ / m 2 It is preferable that the concentration is less than 20 mJ / m 2 It is more preferable that the thickness be less than or equal to 100 nm, because the peel strength of the electrode active material layer from the current collector is increased.
[0031] Surface free energy γ of electrode binder (B) B and each component γ d B , γ p B , γ h BIt is effective to adjust the value of by using, for example, a surfactant. The surfactant will be described in detail later.
[0032] In the present invention, the surface free energy γ of the electrode binder (B) B , and its dispersion force component γ d B , dipole component γ p B , and the hydrogen bond component γ h B is a value calculated by the Kitazaki-Hata theory described in Non-Patent Document 1, and is calculated in detail by the method described below.
[0033] "1-2-2-2. How to calculate surface free energy" We will explain how to calculate the surface free energy of the electrode binder (B). According to the Kitazaki-Hata theory, the following formula holds between the contact angle θ between solid S and liquid L, and the surface free energies of solid S and liquid L.
[0034]
number
[0035] Gamma S is the surface free energy of solid S, γ d S is the dispersion force component, γ p S is its dipole component, γ h S represents its hydrogen bond component. γ L is the surface free energy of liquid L, γ d L is the dispersion force component, γ p L is its dipole component, γ h L represents its hydrogen bond component.
[0036] Each component of the surface free energy of solid S, γ d S , γ p S , γ hS can be calculated by measuring the contact angles with three types of liquids L1, L2, and L3 whose surface free energies are known, and solving the following simultaneous equations with three unknowns.
[0037] The equation that holds between solid S and liquid L1 is as follows.
[0038]
number
[0039] Gamma L1 is the surface free energy of liquid L1, γ d L1 is the dispersion force component, γ p L1 is its dipole component, γ h L1 represents the hydrogen bond component. θ1 represents the contact angle between the solid S and the liquid L1. And γ L1 , γ d L1 , γ p L1 , γ h L1 , θ1 are each a value that is determined in advance.
[0040] The equation that holds between solid S and liquid L2 is as follows.
[0041]
number
[0042] Gamma L2 is the surface free energy of liquid L2, γ d L2 is the dispersion force component, γ p L2 is its dipole component, γ h L2 represents the hydrogen bond component. θ2 represents the contact angle between the solid S and the liquid L2. And γ L2 , γ d L2 , γ p L2, γ h L2 , θ2 are each a value that is determined in advance.
[0043] The equation that holds between solid S and liquid L3 is as follows.
[0044]
number
[0045] Gamma L3 is the surface free energy of liquid L3, γ d L3 is the dispersion force component, γ p L3 is its dipole component, γ h L3 represents the hydrogen bond component. θ3 represents the contact angle between the solid S and the liquid L3. And γ L3 , γ d L3 , γ p L3 , γ h L3 , θ3 are each a value that is determined in advance.
[0046] In the present invention, diiodomethane (γ L1 :50.8mJ / m 2 , γ d L1 :46.8mJ / m 2 , γ p L1 : 4.0mJ / m 2 , γ h L1 :0.0mJ / m 2 ), ethylene glycol (γ L2 : 47.7mJ / m 2 , γ d L2 :30.1mJ / m 2 , γ p L2 :0.0mJ / m 2 , γ h L2 : 17.6mJ / m 2), and distilled water (γ L3 :72.8mJ / m 2 , γ d L3 :29.1mJ / m 2 , γ p L3 : 1.3mJ / m 2 , γ h L3 : 42.4mJ / m 2 ) based on the contact angle determined by the measurement method described below, and the value calculated is regarded as the surface free energy.
[0047] In the above formula, by replacing the solid S with the electrode binder (B), the surface free energy of the electrode binder and its components can be calculated. That is, γ S =γ B , γ d S =γ d B , γ p S =γ p B , γ h S =γ h B It becomes.
[0048] "1-2-2-3. How to measure contact angle" The contact angle is measured by the following steps (i) to (iii). (i) 1 mL of a 10 mass % aqueous solution of the electrode binder (B) is dropped onto a glass plate, and the dropped solution is thinly spread using a 2 mil applicator. (ii) The glass plate coated with the aqueous solution of the electrode binder (B) is dried for 5 minutes in a blower dryer set at 60° C. to form a coating. (iii) After leaving this coating to stand for 2 minutes in an atmosphere of 23°C x 50% Rh, the contact angle is measured using a contact angle meter "CA-VP type" manufactured by Kyowa Interface Science Co., Ltd. by the sessile drop method in accordance with JIS R3257.
[0049] The contact angles θ1, θ2, and θ3 are measured for diiodomethane (liquid L1), ethylene glycol (liquid L2), and distilled water (liquid L3) as droplets in the sessile drop method. These measured values are substituted into equations (2), (3), and (4), respectively, to obtain the surface free energy γ B and each component γ d B , γ p B , γ h B Request.
[0050] "1-2-2-4. Ingredients contained in electrode binder (B)" The electrode binder (B) is a water-soluble binder containing a resin component. The electrode binder (B) preferably contains 95% by mass or more of a water-soluble organic compound. The electrode binder (B) may be composed of one type of compound, or may contain two or more types of compounds. In the electrode, all of the water-soluble compounds contained in the electrode active material layer are components of the electrode binder (B). Note that, when the electrode is incorporated in a non-aqueous secondary battery, components that dissolve in the solvent of the electrolyte are not included in the components that constitute the electrode binder (B).
[0051] The resin component may be a polymer of a compound having an ethylenically unsaturated bond. The polymer of a compound having an ethylenically unsaturated bond may be a polymer of one type of compound or a copolymer of two or more types of compounds. Examples of the compound having an ethylenically unsaturated bond include (meth)acrylic acid and its derivatives, (meth)acrylic acid salts, and other vinyl compounds. Examples of (meth)acrylic acid derivatives include (meth)acrylic acid esters, (meth)acrylamides, (meth)acrylonitrile, and the like. Examples of (meth)acrylic acid salts include alkali metal salts such as sodium (meth)acrylate, and ammonium (meth)acrylate, and the like. Examples of other vinyl compounds include styrene, divinylbenzene, butadiene, N-vinylacetamide, N-vinylformamide, vinyl alcohol, and vinyl acetate, and the like.
[0052] The resin component may contain a resin that functions as a dispersant. The dispersant improves the dispersibility of insoluble components such as the electrode active material (A) and the conductive assistant in the electrode slurry described below, and can disperse the insoluble components better in the electrode active material layer produced using the electrode slurry. As the resin that functions as a dispersant, it is preferable to use a cellulose derivative. This is because, in addition to the above-mentioned effect as a dispersant, the peel strength of the electrode active material layer against the current collector can be improved.
[0053] Examples of cellulose derivatives include carboxymethylcellulose, methylcellulose, and hydroxypropylcellulose, or metal salts thereof. The cellulose derivative may contain any of these compounds alone or may contain a plurality of types. Other cellulose derivatives may also be used. As the cellulose derivative, carboxymethylcellulose or its metal salts are preferred.
[0054] In addition, if the amount of the cellulose derivative is appropriate, the surface free energy γ B , and its dipole component γ p B , and the hydrogen bond component γ h B From this viewpoint, the content of the cellulose derivative in the electrode binder (B) is preferably 8% by mass or more, more preferably 12% by mass or more, and even more preferably 16% by mass or more. From the same viewpoint, the content of the cellulose derivative in the electrode binder (B) is preferably 80% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less.
[0055] The glass transition temperature Tg of the resin component contained in the electrode binder (B) is more preferably 100° C. or higher, and even more preferably 130° C. or higher. Here, the glass transition temperature Tg is the peak top temperature of a DDSC chart, which is a differential of a DSC curve obtained using an EXSTAR DSC / SS7020 manufactured by Hitachi High-Tech Science Corporation. The sample is a 2 mm×2 mm×0.5 mm film obtained by drying an aqueous solution of the resin component, and the measurement is performed while increasing the temperature at 10° C. / min.
[0056] The electrode binder (B) may contain, in addition to the resin component, a surfactant, a polymerization initiator used in the synthesis of the resin component, a catalyst, etc. The surfactant reduces the surface free energy γ B and each component γ d B , γ p B , γ h B It is preferable to use it to effectively adjust the value of
[0057] The content of the surfactant in the electrode binder (B) is preferably 2.5% by mass or more, more preferably 8.0% by mass or more, and even more preferably 20% by mass or more. The surface free energy γ of the electrode binder (B) B , and its dipole component γ p B , and the hydrogen bond component γ h B This is because it is possible to reduce
[0058] The content of the surfactant in the electrode binder (B) is preferably 75 mass % or less, more preferably 50 mass % or less, further preferably 40 mass % or less, and particularly preferably 15 mass % or less, because this allows the peel strength of the electrode active material layer from the current collector and the cycle characteristics of the electrode to be maintained high.
[0059] When a surfactant is used, any of anionic, cationic, amphoteric, and nonionic surfactants may be used, but nonionic surfactants are preferred. p B and hydrogen bond component γ h B However, if the content of the nonionic surfactant is excessive, the peel strength of the electrode active material layer tends to decrease, so it is preferable to adjust the content of the nonionic surfactant in the electrode active material layer in consideration of this point.
[0060] Examples of nonionic surfactants include polyoxyethylene alkyl ether, sorbitan fatty acid ester, glycerin fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene sorbitol fatty acid ester, polyoxyethylene fatty acid ester, polyoxyethylene hydrogenated castor oil, polyoxyethylene alkylamine, etc. The nonionic surfactant may contain any of these compounds alone or may contain a plurality of kinds. Other nonionic surfactants may also be used.
[0061] As the nonionic surfactant, those having a segment composed of an ethylene oxide structure are preferred, and polyoxyethylene alkyl ether is more preferred.
[0062] [1-2-3. Other ingredients] In addition to the above components, the electrode active material layer may contain, as a conductive assistant, carbon black, vapor-grown carbon fiber, etc. Specific examples of vapor-grown carbon fiber include VGCF (registered trademark)-H (Showa Denko K.K.).
[0063] <2. Method for producing non-aqueous secondary battery electrodes> An example of a method for producing a non-aqueous secondary battery electrode will be described below, but the method is not limited to the method described here as long as an electrode having the above configuration can be obtained. In this example, the electrode can be produced by applying the electrode slurry onto a current collector, drying it to obtain an electrode sheet, and then cutting the electrode sheet into an appropriate size and shape as necessary. The electrode slurry contains an electrode active material (A) and an electrode binder (B). The detailed configuration of the electrode slurry will be described later.
[0064] Examples of methods for applying the electrode slurry onto the current collector include the reverse roll method, direct roll method, doctor blade method, knife method, extrusion method, curtain method, gravure method, bar method, dip method, and squeeze method. Among these, the doctor blade method, knife method, and extrusion method are preferred, and application using a doctor blade is more preferred. This is because it is suitable for the physical properties such as viscosity of the electrode slurry and drying property, and a coating film with a good surface condition can be obtained.
[0065] The electrode slurry may be applied to only one side of the current collector, or may be applied to both sides. When the electrode slurry is applied to both sides of the current collector, it may be applied to one side at a time, or to both sides simultaneously. The electrode slurry may be applied to the surface of the current collector continuously or intermittently. The amount and area of application of the electrode slurry may be appropriately determined depending on the size of the battery, etc. The basis weight of the electrode active material layer after drying is 4 to 20 mg / cm. 2 is preferably 6 to 16 mg / cm 2 It is more preferable that:
[0066] The method for drying the applied electrode slurry is not particularly limited, but for example, hot air, vacuum, (far) infrared rays, electron beams, microwaves, and low temperature air can be used alone or in combination. The drying temperature is preferably 40° C. or higher and 180° C. or lower, and the drying time is preferably 1 minute or higher and 30 minutes or lower.
[0067] The electrode sheet in which the electrode active material layer is formed on the current collector may be cut to a size and shape appropriate for an electrode. The method for cutting the electrode sheet is not particularly limited, but for example, slitting, laser cutting, wire cutting, cutter, Thomson cutting, etc. can be used.
[0068] Before or after cutting the electrode sheet, it may be pressed as necessary. This allows the electrode active material to be more firmly attached to the current collector, and the electrode can be made thinner to make the battery more compact. As a pressing method, a general method can be used, and in particular, it is preferable to use a mold pressing method or a roll pressing method. The pressing pressure is not particularly limited, but is preferably 0.5 to 5 t / cm. 2 This is to suppress the influence on the insertion and desorption of charge carriers such as lithium ions into and from the electrode active material (A).
[0069] <3. Electrode slurry> The electrode slurry of the present embodiment contains an electrode active material (A), an electrode binder (B), and an aqueous medium. The electrode slurry may contain a conductive assistant and the like as necessary.
[0070] In the electrode slurry, the electrode binder (B) is preferably dissolved in an aqueous medium. This is because the electrode binder (B) is likely to form a uniform layer on the particle surface of the electrode active material (A) after the slurry is dried. The aqueous medium contained in the electrode slurry is water, a hydrophilic solvent, or a mixture thereof.
[0071] The non-volatile content of the electrode slurry is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more. This is to form a larger amount of electrode active material layer with a smaller amount of electrode slurry. The non-volatile content of the electrode slurry is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less. This is to facilitate the preparation of the electrode slurry.
[0072] The contents of the electrode active material (A) and the electrode binder (B) in the non-volatile matter of the electrode slurry are the same as the contents of the electrode active material (A) and the electrode binder (B) in the electrode active material layer, respectively, as described above in the description of the non-aqueous secondary battery electrode.
[0073] <4. Manufacturing method of electrode slurry> An example of a method for producing an electrode slurry is a method in which the electrode active material (A), the electrode binder (B), and other components added as necessary are mixed by adding them to an aqueous medium. In this case, the order in which each component is added may be appropriately adjusted so that each component is easily dissolved or dispersed in the aqueous medium, or two or more components may be mixed in the solid phase and then the mixture may be added to the aqueous medium. The mixing method in each step is not particularly limited, and examples thereof include a method in which the necessary components are mixed using a mixing device such as a stirring type, a rotating type, or a shaking type. In addition, the order in which each component is added to be mixed is also not particularly limited.
[0074] Another example of the method for producing the electrode slurry is a method in which a binder solution in which the electrode binder (B) is dissolved in an aqueous medium is mixed with the electrode active material (A) and, if necessary, other components. Examples of the mixing method are the same as those described above.
[0075] <5.Nonaqueous secondary battery> In the non-aqueous secondary battery according to the present embodiment, it is preferable that an alkali metal ion is used as the charge carrier, and it is more preferable that a lithium ion is used as the charge carrier. Hereinafter, as a preferred example of the non-aqueous secondary battery according to the present embodiment, a battery in which the charge carrier is lithium ion, i.e., a lithium ion secondary battery, will be described, but the configuration of the battery is not limited to that described here. The lithium ion secondary battery according to the example described here is a battery in which a positive electrode, a negative electrode, an electrolyte, and, if necessary, components such as a separator are housed in an exterior body, and the non-aqueous secondary battery electrode produced by the above method is used for one or both of the positive electrode and the negative electrode.
[0076] [5-1. Electrolyte] As the electrolyte, a non-aqueous liquid having ion conductivity is used. Examples of the electrolyte include a solution in which an electrolyte is dissolved in an organic solvent, an ionic liquid, etc., with the former being preferred. As the electrolyte, a solution in which an alkali metal salt described below is dissolved in an organic solvent (also referred to as an "organic solvent solution of an alkali metal salt") is more preferred. This is because a non-aqueous secondary battery having low manufacturing costs and low internal resistance can be obtained.
[0077] As the electrolyte, it is preferable to use an alkali metal salt, and it can be appropriately selected depending on the type of electrode active material, etc. Examples of the electrolyte include LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, lithium aliphatic carboxylates, etc. Other alkali metal salts can also be used as the electrolyte.
[0078] The organic solvent for dissolving the electrolyte is not particularly limited, but examples thereof include carbonate ester compounds such as ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC), nitrile compounds such as acetonitrile, and carboxylate esters such as ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate. Among these compounds, it is preferable to use an organic solvent consisting of one or more kinds selected from the group consisting of carbonate ester compounds, nitrile compounds, and carboxylate esters. These organic solvents may be used alone or in combination of two or more kinds.
[0079] [5-2. Exterior body] The exterior body may be, for example, a laminate of aluminum foil and a resin film, but is not limited to this. The shape of the battery may be any shape, such as a coin type, a button type, a sheet type, a cylindrical type, a rectangular type, or a flat type. EXAMPLES
[0080] In the following examples, an electrode binder (B) for a lithium ion secondary battery, a negative electrode, and a lithium ion secondary battery are prepared as an example of the configuration of the present invention, and the effects of the present invention are confirmed by comparing with comparative examples. Note that the present invention is not limited to the examples.
[0081] <1. Synthesis of Copolymer (P)> (Synthesis Examples 1 to 8) The copolymers (P1) to (P8) were produced in the same manner. A separable flask equipped with a condenser, a thermometer, a stirrer, and a dropping funnel was charged with 100 parts by mass of a monomer having the composition shown in Table 1, 0.2 parts by mass of 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 0.05 parts by mass of ammonium persulfate, and 693 parts by mass of water at 30°C. The mixture was heated to 80°C and polymerized for 4 hours. The mixture was then cooled to room temperature, dried, and pulverized to obtain the powdered copolymers (P1) to (P8), respectively.
[0082] [Table 1]
[0083] <2. Preparation of negative electrode slurry> In all of the Examples and Comparative Examples, the components were mixed in the ratio shown in Table 2 to prepare a negative electrode slurry. The mixing method was as follows: 37.65 parts by mass of SCMG (registered trademark)-XRs (manufactured by Showa Denko K.K.), 9.60 parts by mass of silicon monoxide (SiO) (manufactured by Sigma-Aldrich) as the negative electrode active material, a total of 2.25 parts by mass of each component (shown in Tables 3 and 4) contained in the electrode binder (B), 0.50 parts by mass of VGCF (registered trademark)-H (Showa Denko K.K.), and 23.5 parts by mass of water were added, and the mixture was kneaded at 2000 rpm for 4 minutes using a stirring mixer (rotating and revolving stirring mixer). 26.5 parts by mass of water was further added, and the mixture was further mixed at 2000 rpm for 4 minutes to prepare a negative electrode slurry.
[0084] [Table 2]
[0085] [Table 3]
[0086] [Table 4]
[0087] In Tables 3 and 4 *1: CMC Daicel 1110: Daicel Corporation, etherification degree 0.7, 2% viscosity 100-200 (mPa s) *2: CMC Daicel 1190: Daicel Corporation, etherification degree 0.7, 1% viscosity 1300-2000 (mPa s) *3 and *4: Both manufactured by Kao Corporation *5: Hitenol (registered trademark) 08E: Manufactured by Daiichi Kogyo Seiyaku Co., Ltd. *6: Kachiogen (registered trademark) TML: manufactured by Daiichi Kogyo Seiyaku Co., Ltd.
[0088] <3. Surface free energy of electrode binder (B)> In each of Examples 1 to 9 and Comparative Examples 1 to 9, an aqueous solution containing 10 mass % of the composition shown in Tables 3 and 4 was prepared. Using this aqueous solution, a film of each electrode binder (B) was formed on a glass plate by the method described above in the description of the method for measuring the contact angle.
[0089] Using the obtained coating of each electrode binder (B), the contact angles were measured for diiodomethane, ethylene glycol, and water by the above method. The measured contact angle values were used to solve the three-dimensional simultaneous equations consisting of the above formulas (2) to (4) to obtain the dispersion force component γ d B , dipole component γ p B , hydrogen bond component γ h B The surface free energy γ B (=γ d B +γ p B +γ h B ) was sought.
[0090] For the electrode binder (B) in each example and comparative example, γ d B , γ p B , γ h B , and γ B are shown in Tables 3 and 4.
[0091] <4. Battery Construction> [4-1. Preparation of negative electrode] The negative electrode slurry prepared in each Example and Comparative Example was applied to one side of a copper foil (current collector) having a thickness of 10 μm, with a weight per unit area of 8 mg / cm2 after drying. 2 The negative electrode slurry was applied using a doctor blade so that the negative electrode slurry was applied to the copper foil. The copper foil to which the negative electrode slurry was applied was dried at 60°C for 10 minutes, and then further dried at 100°C for 5 minutes to produce a negative electrode sheet on which a negative electrode active material layer was formed. This negative electrode sheet was pressed using a mold press at a pressure of 1 t / cm. 2 The pressed negative electrode sheet was cut into a size of 22 mm × 22 mm, and a conductive tab was attached to prepare a negative electrode.
[0092] [4-2. Preparation of the positive electrode] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 90 parts by mass of O2, 5 parts by mass of acetylene black, and 5 parts by mass of polyvinylidene fluoride were mixed, and then 100 parts by mass of N-methylpyrrolidone was mixed to prepare a positive electrode slurry (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The O2 fraction is 0.90).
[0093] The prepared positive electrode slurry was applied to one side of an aluminum foil (current collector) with a thickness of 20 μm so that the weight per unit area after drying was 22.5 mg / cm 2 The positive electrode slurry was applied using a doctor blade so that the positive electrode slurry was applied to the aluminum foil. The aluminum foil to which the positive electrode slurry was applied was dried at 120°C for 5 minutes, and then pressed by a roll press to prepare a positive electrode sheet on which a positive electrode active material layer having a thickness of 100 μm was formed. The obtained positive electrode sheet was cut into a size of 20 mm x 20 mm, and a conductive tab was attached to prepare a positive electrode.
[0094] [4-3. Preparation of electrolyte] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and fluoroethylene carbonate (FEC) were mixed in a volume ratio of 30:60:10. LiPF6 was dissolved in the resulting mixed solvent to a concentration of 1.0 mol / L and vinylene carbonate (VC) to a concentration of 1.0 mass % to prepare an electrolyte solution.
[0095] 4-4. Battery assembly The positive and negative electrodes were arranged so that the positive and negative active material layers faced each other with a separator made of a polyolefin porous film interposed therebetween, and the resulting battery was housed in a laminated exterior body (battery pack) made of aluminum foil and a resin film. An electrolyte was injected into the exterior body, which was then packed with a vacuum heat sealer to obtain a lithium ion secondary battery.
[0096] <5. Evaluation> The electrode performance and battery performance of the electrodes and batteries produced in each of the Examples and Comparative Examples were evaluated. The evaluation methods were as follows, and the evaluation results are shown in Tables 3 and 4.
[0097] [5-1. Number of cracks in the negative electrode active material layer] The appearance of the surface of the negative electrode sheet after the pressing step was visually checked, and the number of cracks in a rectangular area of 5 cm x 20 cm was counted.
[0098] [5-2. Peel strength of negative electrode active material layer] Using the negative electrode sheet after the pressing process, the peel strength of the negative electrode active material layer was measured in an atmosphere of 23°C and 50% relative humidity by mass throughout the entire process. The test machine used was Tensilon (registered trademark, manufactured by A&D Co., Ltd.). The negative electrode sheet was cut into a piece 25 mm wide and 70 mm long to prepare a test piece. The negative electrode active material layer on the test piece was attached to a SUS plate 50 mm wide and 200 mm long using double-sided tape (NITTOTAPE (registered trademark) No. 5, manufactured by Nitto Denko Co., Ltd.) so that the center of the test piece and the center of the SUS plate were aligned. The double-sided tape was attached so as to cover the entire area of the test piece.
[0099] After leaving the test piece and the SUS plate in a state of being stuck together for 10 minutes, the copper foil was peeled off from the negative electrode active material by 20 mm from one end of the test piece in the length direction, folded back by 180°, and the peeled copper foil part was held by the upper chuck of the tester. Furthermore, one end of the SUS plate from which the copper foil was peeled off was held by the lower chuck. In this state, the copper foil was peeled off from the test piece at a speed of 100±10 mm / min, and a graph of peel length (mm)-peel force (mN) was obtained. In the obtained graph, the average value (mN) of the peel force at a peel length of 10 to 45 mm was calculated, and the value obtained by dividing the average value of the peel force by the width of the test piece, 25 mm, was taken as the peel strength (mN / mm) of the negative electrode active material layer. In any of the examples and comparative examples, peeling between the double-sided tape and the SUS plate and interfacial peeling between the double-sided tape and the negative electrode active material layer did not occur during the test.
[0100] 5-3. Battery discharge capacity retention rate (cycle characteristics) The charge and discharge cycle test of the battery was carried out under the condition of 25°C according to the following procedure. First, the battery was charged at a current of 1C until the voltage reached 4.2V (CC charging), and then charged at a voltage of 4.2V until the current was 1 / 20C (CV charging). After leaving the battery for 30 minutes, the battery was discharged at a current of 1C until the voltage reached 2.75V (CC discharging). A series of operations of CC charging, CV charging, and CC discharging is defined as one cycle. The sum of the time integral values of the current in the CC charging and CV charging in the nth cycle is defined as the charge capacity (mAh) in the nth cycle, and the time integral value of the current in the CC discharging in the nth cycle is defined as the discharge capacity (mAh) in the nth cycle. The discharge capacity retention rate of the battery in the nth cycle is the ratio (%) of the discharge capacity in the nth cycle to the discharge capacity in the 1st cycle. In this embodiment and the comparative example, the discharge capacity retention rate in the 100th cycle was evaluated.
[0101] [5-4. Internal resistance (DCR)] The internal resistance (DCR (Ω)) of the battery was measured at 25°C using the following procedure. The battery was charged at a constant current of 0.2C from the rest potential to 3.6V, and the state of charge was set to 50% of the initial capacity (SOC50%). The battery was then discharged for 60 seconds at current values of 0.2C, 0.5C, 1C, and 2C. The DCR (Ω) at SOC50% was determined from the relationship between these four current values (values over 1 second) and voltage.
[0102] <6. Evaluation Results> The electrode binder (B) in each of the Examples and Comparative Examples contains at least a resin component. The electrode binder (B) in each of the Examples and Comparative Examples is water-soluble. Hereinafter, the surface free energy γ B and each of its components γ d B , γ p B , γ h B We will consider the relationship between these and the numerical values obtained in each evaluation.
[0103] [6-1. Appearance of electrode (number of cracks)] 1 to 4 show the surface free energy γB and each of its components γ d B , γ p B , γ h B 1 is a diagram in which the number of cracks in the electrode active material layer is plotted against the temperature, in which working examples are indicated by a black circle and comparative examples are indicated by an x.
[0104] As can be seen from Figures 1 to 4, the surface free energy γ B is 70mJ / m 2 and the dipole component of the surface free energy γ p B is 26 mJ / m 2 If it is equal to or less than this, the electrode binder (B) can suppress the occurrence of cracks in the electrode active material layer.
[0105] [6-2. Peel strength of electrode active material layer] 5 to 8 show the surface free energy γ B and each of its components γ d B , γ p B , γ h B 1 is a diagram in which values of peel strength of an electrode active material layer are plotted against each other, in which working examples are indicated by a black circle and comparative examples are indicated by an x.
[0106] As can be seen from Figures 5 to 8, the surface free energy γ B is 70mJ / m 2 and the dipole component of the surface free energy γ p B is 26 mJ / m 2 If it is equal to or less than this, an electrode active material layer having high peel strength can be formed by the electrode binder (B).
[0107] [6-3. Discharge capacity maintenance rate] 9 to 12 show the surface free energy γ B and each of its components γ dB , γ p B , γ h B 9 to 12 are diagrams in which values of the discharge capacity retention rate of the battery are plotted against the discharge capacity retention rate of the battery. In this diagram, working examples are indicated with a black circle, and comparative examples are indicated with an X. Note that since it was impossible to measure the discharge capacity retention rate of comparative examples 6 and 7, plots corresponding to these comparative examples are not shown in FIGS.
[0108] As can be seen from Figures 9 to 12, the surface free energy γ B is 70mJ / m 2 and the dipole component of the surface free energy γ p B is 26 mJ / m 2 If it is equal to or less than this, a battery having a high discharge capacity retention rate can be obtained by using the electrode binder (B).
[0109] [6-4. Battery internal resistance (DCR)] 13 to 16 show the surface free energy γ B and each of its components γ d B , γ p B , γ h B 1 is a diagram in which the DCR values of the battery are plotted against the temperature, in which working examples are indicated by ● and comparative examples are indicated by ×.
[0110] As can be seen from Figures 13 to 16, the surface free energy γ B is 70mJ / m 2 and the dipole component of the surface free energy γ p B is 26 mJ / m 2 If the DCR is less than 100%, it is understood that a battery having a low DCR can be obtained by using the electrode binder (B).
[0111] Furthermore, as can be seen from Figures 13 to 16, in order to obtain a battery with a low DCR, the surface free energy γ B is 70mJ / m2 and the dipole component of the surface free energy γ p B is 26 mJ / m 2 It turns out that it needs to be the following:
[0112] [6-5. Conclusion] To sum up the above results, it can be said that by using the nonaqueous secondary battery electrode binder (B) of the present invention, a secondary battery can be obtained which has an electrode active material layer with fewer cracks and high peel strength from the current collector, and which also has low internal resistance and good cycle characteristics.
Claims
1. A method for producing a non-aqueous secondary battery electrode slurry, comprising the step of mixing an electrode active material (A), an electrode binder (B), and an aqueous medium, The electrode binder (B) is composed of a water-soluble component containing a resin component, The electrode binder (B) has a surface free energy γ B of 70 mJ / m 2 or less at 23° C.; The method for producing a non-aqueous secondary battery electrode slurry, wherein the dipole component γ p B of the surface free energy is 26 mJ / m 2 or less.
2. The surface free energy γ B is 66 mJ / m 2 The method for producing a non-aqueous secondary battery electrode slurry according to claim 1, wherein:
3. The dipole component γ of the surface free energy p B is 22 mJ / m 2 The method for producing a non-aqueous secondary battery electrode slurry according to claim 1 or 2, wherein the non-aqueous secondary battery electrode slurry is:
4. The hydrogen bond component γ of the surface free energy h B is 24 mJ / m 2 The method for producing a nonaqueous secondary battery electrode slurry according to any one of claims 1 to 3, wherein the nonaqueous secondary battery electrode slurry is:
5. 5. The method for producing a non-aqueous secondary battery electrode slurry according to claim 1, wherein the resin component contains a polymer of a compound having an ethylenically unsaturated bond.
6. A method for producing a non-aqueous secondary battery electrode including a current collector and an electrode active material layer, comprising: A step of mixing an electrode active material (A), an electrode binder (B), and an aqueous medium to obtain an electrode slurry; and applying the electrode slurry onto a current collector and drying the electrode slurry to obtain the electrode active material layer. The electrode binder (B) is composed of a water-soluble component containing a resin component, The electrode binder (B) has a surface free energy γ B of 70 mJ / m 2 or less at 23° C.; The method for producing a non-aqueous secondary battery electrode, wherein the dipole component γ p B of the surface free energy is 26 mJ / m 2 or less.
7. The method for producing a nonaqueous secondary battery electrode according to claim 6 , wherein the electrode active material layer contains 85% by mass or more and 99% by mass or less of the electrode active material (A).
8. The method for producing a non-aqueous secondary battery electrode according to claim 6 or 7, wherein the electrode active material (A) contains a material containing elemental Si and a carbon material.
9. The method for producing a nonaqueous secondary battery electrode according to any one of claims 6 to 8, wherein a peel strength of the electrode active material layer from the current collector is 30 mN / mm or more.
10. The method for producing a non-aqueous secondary battery electrode according to claim 6, wherein the surface free energy γ B is 66 mJ / m 2 or less.
11. The method for producing a non-aqueous secondary battery electrode according to claim 6, wherein the dipole component γ p B of the surface free energy is 22 mJ / m 2 or less.
12. The method for producing a non-aqueous secondary battery electrode according to claim 6, wherein the hydrogen bond component γ h B of the surface free energy is 24 mJ / m 2 or less.
13. The method for producing a non-aqueous secondary battery electrode according to claim 6, wherein the resin component includes a polymer of a compound having an ethylenically unsaturated bond.
Citation Information
Patent Citations
Adhesive for lithium ion battery
CN105504169A
Evaluating method for battery component and battery material selected by this method
JP1999219708A
Positive electrode slurry for secondary battery, method for manufacturing the same, method for manufacturing positive electrode for secondary battery, and lithium ion secondary battery
JP2013149396A
Mixture ink for secondary battery electrode formation
JP2015023015A
Copolymer for binders for nonaqueous battery electrodes, slurry for nonaqueous battery electrodes, nonaqueous battery electrode, and nonaqueous battery
WO2017150200A1